ANALISIS PENGARUH MOBIL LISTRIK TERHADAP PENJUALAN MOBIL INTERNAL COMBUSTION ENGINE (ICE) BERDASAR UJI ANOVA - Wilson Patrick Tirtamidjaja; Anjerina Hartanto Widjaya; Claudia Glory Marchatmyna; Lina Gozali; Meirista Wulandari (Jurnal Mitra Teknik Industri, 2026)
The purpose of this paper was to determine whether Indonesian sales of internal combustion engine (ICE) vehicles are impacted by the growth in electric vehicle sales. The Association of Indonesian Automotive Industries' (GAIKINDO) publicly available wholesales reports for the years 2020–2024 provided the data used in the analysis. The association between the sales of the electric vehicle (X variable) dan the sales of the ICE vehicle (Y variable) was investigated quantitatively using simple regression analysis dan the F-test. The test results show that the significance value is greater than 0.05, with a value of 0.729. Therefore, it can be stated that the data distribution is normal. Then, the Spearman's Rank Correlation Test was performed, yielding a correlation coefficient value of -0.545, which means the two variables have a strong negative relationship; when one variable increases, the other will decrease. The significance value of the Spearman's rank correlation test performed was 0.067, which is below 0.1 as the P-Value. Next, the F-test was performed, resulting in an F-statistic value of 5.026, which, when compared to the F-table, is 4.96 (F-statistic ≥ F-table). From the 3 tests conducted, it can be concluded that H0 is accepted, meaning that the sale of electric cars significantly affects the sale of ICE (Internal Combustion Engine) cars.